Capabilities and Operation of the FAAM EZLidar - Mareno, Franco (Zenodo, 2010)
The FAAM EZLidar is one of the most valuable instruments on the FAAM aircraft, which was (for example) used to measure volcanic ash in the Eyjafjallajökull ash cloud in April 2010. This document (Observation Based Research (OBR) Technical Note 79) gives in depth information about the capabilities and operation of the instrument. Previously curated at: http://cedadocs.ceda.ac.uk/785/ The publish date on this item was its original published date. Main files in this record: capabilities_and_operation_of_the_faam_ezlidar.pdf Item originally deposited with Centre for Environmental Data Analysis (CEDA) document repository by Mr Jurgen Reinecke. Transferred to CEDA document repository community on Zenodo on 2022-11-24